Nucleotide sequence definition of a major human repeated DNA, the Hind III 1.9 kb family. - Manuelidis, L (1982)
A human Hind III 1.9 kb repeated DNA fragment was isolated and cloned in pBR322. A cloned member that hybridized predominantly to the 1.9 kb Hind III band in a digest of whole human DNA was chosen for sequencing. It is an 1894 bp fragment that shows no significant internal repeats. Few pCG residues are observed in the sequence and there are numerous stop codons. Detailed sequence comparisons confirm this is a novel class of repeats that is not related to previously characterized human satellite DNAs or Alu sequences. At least a portion of the sequence described is conserved in evolution.